Cellulose ionogels, a perspective of the last decade: A review. (15th November 2021) - Hopson, Cynthia; Villar-Chavero, M. Mar; Domínguez, Juan C.; Alonso, M. Virginia; Oliet, Mercedes; Rodriguez, Francisco
Abstract: Cellulose ionogels have been extensively studied due to the variability of their properties and applications. The capability of trapping an ionic liquid in a biodegradable solid matrix without losing its properties makes this type of material a promising substitute for fossil fuel-derived materials. The possibility to formulate ionogels chemically or physically, to choose between different ionic liquids, cellulose types, and the possibility to add a wide range of additives, make these ionogels an adaptable material that can be modified for each target application in many fields such as medicine, energy storage, electrochemistry, etc. The aim of this review is to show its versatility and to provide a summary picture of the advances in the field of cellulose ionogels formulation (chemical or physical methods), as well as their potential applications, so this review will serve as a stimulus for research on these materials in the future. Highlights: Cellulose ionogels in the last ten years Physical and chemical ionogels, differences and evolution Cellulose ionogels applications and future trend